Facilitating Large Language Model Russian Adaptation with Learned Embedding Propagation - Михаил Тихомиров; Даниил Чернышев (Journal of Language and Education)
Background: Recent advancements in large language model (LLM) technologies have introduced powerful open-source instruction-tuned LLMs that match the text generation quality of leading models like GPT-4. Despite accelerating LLM adoption in sensitive-information environments, the lack of disclosed training data hinders replication and makes these achievements exclusive to specific models.